Geographical variation in HIV testing in South Africa: Evidence from the 2017 national household HIV survey - Sean Jooste; Musawenkosi Mabaso; Myra Taylor; Alicia North; Yolande Shean; Leickness C. Simbayi; Tarylee Reddy; Leonard Mwandingi; Tenielle Schmidt; Portia Nevhungoni; Samuel Manda; Khangelani Zuma (Southern African Journal of HIV Medicine, 2021)
Background: Identification of the geographical areas with low uptake of HIV testing could assist in spatial targeting of interventions to improve the uptake of HIV testing.